“THE EFFECT OF ERBIUM IONS ON SEMICONDUCTOR PHOTODETECTORS: A SILICON MODEL” (Scientific journal of the Fergana State University, 2025)
This article explores the potential of improving the efficiency of semiconductor photodetectors by doping silicon with erbium ions. During the study, photoluminescence and photo-conductivity spectra were analyzed, and the impact of erbium ions on the optical and electrical properties of silicon was examined. The results suggest that silicon doped with erbium can serve as an effective material for optoelectronic devices, particularly for photodetectors operating in the infrared range.